Determination of Sengon Stand Density Index in the Community Forests (Kranggan and Pringsurat Sub District, Temanggung District) - Ronggo Sadono; Aziz Umroni (Jurnal Ilmu Kehutanan)
Stand Density Index (SDI) reflects stand productivity. Research on density index in community forest is very rare. The objective of this research was to determine stand density index in community forest by implementing Reineke’s density index. There were 62 sample plots established representing density variation, management pattern, and land terrain. Stem diameter of saplings, poles and trees was measured in every plot. Allometry analysis was employed to draw the relation between the number of stem per hectare (N) and stem diameter at the average of basal area (dlbds ). The result showed that the Reineke’s density index could be applied with an adjustment in the reference stem diameter. Based on the accepted allometry coefficient and the minimum stem diameter at the average basal area of 20 cm, the equation of stand density index for community forest is proposed as follows: